Macrophage tracking with USPIO imaging and T2 mapping predicts immune rejection of transplanted stem cells - Wenhui Wang; Zhenyu Liu; Jiahong Zhu; Haocheng Zhen; Meiling Qi; Jing Luo; Junping Zhen (Scientific Reports)
Abstract To develop a clinical imaging method for monitoring macrophage migration to the defect site after implantation of various stem cells and evaluating immune responses in the context of knee arthritis, T2 mapping was correlated with CD68-positive cell densities in defects and the bone marrow. This study, which was approved by the Institutional Animal Care and Use Committee, used 32 New Zealand white rabbits preloaded with ultrasmall superparamagnetic iron oxide particles (USPIOs). They were divided into groups that received different stem cell implants after osteochondral defect induction. T2 imaging was performed using a 3.0 T MR scanner, and the data were analysed via one-way ANOVA, with CD68 expression assessed via immunohistochemistry. After implantation, the T2 signal intensity increased across groups, with subgroup D1 (implantation of rat bone marrow stem cells (BMSCs)) showing the lowest T2 value early and the steepest increase in T2 values. Notable differences in CD68-positive cell density were found between Subgroup D1 and the other groups and between Subgroups A1 and C1 post-surgery. A moderate negative correlation was observed between T2 signals and CD68-positive cell density in defects (r = -0.468, p = 0.001), whereas a weak correlation was detected in the bone marrow (r = 0.096, p = 0.313). A significant link was identified between CD68-positive cell density in the bone marrow and in defects (r = -0.255, p = 0.001). This study revealed significant differences in immune responses to stem cells from different origin tissues in the context of cartilage repair. Adipose-derived stem cells (ADSCs) were found to be more likely to provoke immune rejection than were BMSCs in the repair of femoral condyle cartilage defects. Compared with allogeneic transplants, xenogeneic mesenchymal stem cell transplants were associated with prolonged immune rejection. T2 mapping technology was effective in predicting the density of CD68-positive cells, providing a valuable tool for immune monitoring in stem cell therapy.